Assessment of Nutrient Usage and Discharge in Tomato Greenhouse. Issue 1 (November 2021) - Suffian, N M; Nguyen, M N; Yokota, K; Inoue, T
Abstract: One of the contributors to eutrophication is from agricultural wastewater which contained nutrients such as nitrogen and phosphorus. The agricultural industry in Japan has practice greenhouse plantation recently. In this study, the amount of nutrient concentration and load in the wastewater were investigated. Water samples from water supply, soil medium and effluent were collected at a greenhouse in Japan which cultivated tomato plants in coconut husk medium. The assessment was conducted every two weeks for regular monitoring for three months. The results showed that concentrations of all nutrients have same concentration level in the water supply samples from January 13 th to March 15 th . The concentration of supplied nutrient on March 29 th increased due to high concentration of nutrients in medium water samples which preventing the nutrient uptake by the plant. The nutrient uptake by the plants were in the same range which NH4 -N was between 13.6 mg/L to 14.99 mg/L, NO2 -N was between 2.3 to 2.5 mg/L, NO3 -N was between 135.9 mg/L to 152.5 mg/L and PO4 -P was between 70.12 to 76.64 mg/L. The concentration of nutrients in drainage was below the permissible limit of Japan's Effluent Standard. As a result, it can be concluded that using greenhouses as an alternative farming method contributes in reducing nutrient discharge by controlling the nutrient supply to the plants.